2016
DOI: 10.22159/ajpcr.2016.v9i5.11711
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Stress, Anxiety, and Depression Among Hypertensive Patients Attending Cardiac Outpatient Department in a Super Specialty Hospital

Abstract: Objective: Hypertension is a major risk factor for cardiovascular disease and its association with negative emotions may increase their risk forthe development of mental health disorders. The main objective of the study was to assess the awareness, stress, anxiety, and depression amonghypertensive patients attending cardiac outpatient department (OPD).Methods: This study was conducted in cardiac OPD of Super Speciality Hospital associated with Government Medical College, Jammu, for a period of1-month commencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…1 Hypertension has a multifactorial etiology, which combines the influence of both environmental and genetic factor. 2 Hypertension is one of the most powerful and independent modifiable risk factor for the development of all the major cardio vascular diseases (CVD) that commonly affects the elderly like coronary artery disease (CAD), peripheral artery disease (PAD), stroke, heart failure and renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…1 Hypertension has a multifactorial etiology, which combines the influence of both environmental and genetic factor. 2 Hypertension is one of the most powerful and independent modifiable risk factor for the development of all the major cardio vascular diseases (CVD) that commonly affects the elderly like coronary artery disease (CAD), peripheral artery disease (PAD), stroke, heart failure and renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…In medical literature, HTN often coined as 'silent killer' since it does not cause any severe symptoms to appear [5]. However, a cross-sectional study performed in Jammu has concluded that most of the hypertensive patients (72.5%) were concerned about the symptoms [6], alternatively, another study conducted in Kerala has suggested that the majority of hypertensive patients lack the knowledge on stroke prevention [7]. Although cardiac walking and laughter therapy has recently been found as maintaining optimum blood pressure in HTN patients [8,9], one of the major successes in medicine in the past decades was the treatment of HTN.…”
Section: Introductionmentioning
confidence: 99%
“…If the pressure is high, it is harder to pump the blood from the heart [1]. HTN has a multifactorial etiology, which combines both environmental and genetic factors [2]. HTN is one of the risk factors for the development of all the major cardiovascular diseases such as coronary artery disease, peripheral artery disease, stroke, heart failure, and renal failure which commonly affect the elderly [3].…”
Section: Introductionmentioning
confidence: 99%